Bimbingan Guru Pendidikan Agama Islam dan Budaya Religius dalam Membina Kedisiplinan Ibadah Siswa - Abu Husein Ibrahim Al 'Ithriy; Joko Subando (Lembaga Yasin AlSys, 2026)
Students’ worship discipline is an important aspect of Islamic education that requires continuous development through the role of teachers and the strengthening of the school environment. This study aims to examine the synergy between the guidance of Islamic Religious Education (PAI) teachers and the school’s religious culture in fostering students’ worship discipline at SMP El Dzikr Islamic Boarding School. This study used a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation studies, and were then analyzed descriptively and qualitatively. The results show that the guidance of PAI teachers, which encompasses cognitive, affective, and psychomotor dimensions, serves as an effective personal intervention when integrated with the school’s religious culture. This synergy is manifested through program coordination, consistency of values, and the collective exemplary conduct of all members of the school community in shaping students’ worship habits. The conclusion of this study affirms that fostering worship discipline cannot be sufficiently carried out through teachers’ individual guidance alone, but must be supported by a religious culture that is living, consistent, and internalized within the school environment. The implications of this study indicate the importance for Islamic educational institutions to integrate PAI teacher guidance with the development of religious culture in a systematic, measurable, and sustainable manner.